Adaptation of account registers of small enterprise subjects to the requirement for the common activity account. (Economics and region, 2018)
The article presents the results of adaptation of accounting registers of small businesses according to the requirements of the updated simplified chart of accounts. Presented forms of accounting registers and the methods of their preparation can be used by small businesses in practice for accounting in a simplified form.
Keywords: small businesses; a simplified chart of accounts; a simplified form of accounting; accounting registers